Nutritional and Antinutritional Analysis of Dawadawa Condiment in Aliero Local Government, Kebbi State, Nigeria - Ahmad, A; Keta, J.N.; Singh, Dharmendra; Hassan, S.R; Ibrahim, M (Journal of Sustainability and Environmental Management, 2022)
Dawadawa is among the most important soup ingredients in Aliero, Kebbi State, Nigeria. The locally produced condiment is being prepared and used to add flavor to soup for many decades without the scientific knowledge of its nutritional and anti-nutritional contents. This study aimed to analyze the proximate and antinutrional contents of Dawadawa in Aliero Local Government, Kebbi State, Nigeria. Five samples from each four collection areas were collected and transported to Botany Laboratory, Kebbi State University of Science and Technology Aliero for analysis. Analysis of the proximate and antinutrient parameters were carried out using the AOAC (Association of Official Analytical Chemists) recommended techniques. The result of the study revealed that the condiments had high moisture contents (33.34 + 2.09) followed by protein (29.37 + 1.31), fibre (13.07 + 0.54), carbohydrate (12.83 + 1.34), lipid (8.92 + 1.75) and ash (2.49 + 0.83). While the results antinutrional analysis revealed that that Cyanide has the highest composition (4.81 + 0.33) followed by Oxalate (4.07 + 0.50), Phytate (3.01 + 0.19) and Saponins (2.90 + 0.36). It was found that Dawadawa condiments have high nutritional contents with low level of antinutrients. In view of the high nutriental content and low antinutriental content, it is recommended that Dawadawa should be used as substitute to the monosodium glutamate-based seasoning salts.